If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 46 + -3x = 10 Solving 46 + -3x = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-46' to each side of the equation. 46 + -46 + -3x = 10 + -46 Combine like terms: 46 + -46 = 0 0 + -3x = 10 + -46 -3x = 10 + -46 Combine like terms: 10 + -46 = -36 -3x = -36 Divide each side by '-3'. x = 12 Simplifying x = 12
| A+6=18 | | (y+4)(y+14)-y(y+10)=216 | | (3y+1)27= | | x(x-2)+2(2x-1)=x^2+4 | | 46-2x=2 | | -19+9Y-Y+6= | | 7x+33+11x+21=180 | | (x-x^2)-(2x^2+x-1)=5+2x-3x^2 | | .5m=0 | | 3y+3=x | | f(-6)=3-4(-6) | | (5v-2)(6v-4)= | | =x^2+2x-4 | | 15u+14=2(5u+6) | | 10+3(2xz)+2xz= | | X-(3x+5)=14 | | 7y-14=4-2y | | 0=x+4 | | 5x+14-2x=-9(4x+2) | | 7(6y-9)=2y | | y=3-4x | | .05x=-1 | | -13b+-17b+32b= | | -3x-3(0)=9 | | 5p+4(4p+6)+p= | | -4Y-15-2Y+2= | | -3(0)-3y=9 | | t^2-3t=54 | | t^2-3d=54 | | (3y+2)/4=7 | | -3x-5(0)=-30 | | -3(0)-5y=-30 |